479 The association of QTc and QT Variability with Severity of Sleep Disordered Breathing. (3rd May 2021) - Patel, Salma; Zareba, Wojciech; Couderc, Jean-Philippe; Xia, Xiaojuan; Woosley, Raymond; Patel, Imran; Combs, Daniel; Mashaqi, Saif; Parthasarathy, Sairam
Abstract: Introduction: The apneas and hypopneas that characterize sleep-disordered breathing (SDB) are associated with QTc prolongation and increased QT variability. There have been mixed results as to whether QTc and QT variability increase with increasing SDB severity. This study assesses whether QTc prolongation and QT variability are likely to increase with increasing severity of SDB in a large multi-center cohort. Methods: 200 subjects with no SDB and approximately 600 with three levels of SDB (mild, moderate, severe) were randomly selected from the Sleep Heart Health study and matched by age, gender and BMI. SDB was defined as an apnea/hypopnea index ≥5. Respiratory and electrocardiograms (ECG) signals from polysomnography studies were analyzed. Bazett's heart rate correction was used to calculate QTc. QT variability was measured as standard deviation of QT intervals (SDQT) and short-term interval QT variability (STVQT), at 5-minute intervals. Subjects were excluded if there were missing data or low-quality ECG. Results: Seven hundred and seventy-one subjects (age 68±10 years, 51% female, 92% Caucasian) were included. One hundred and sixty-five subjects had no SDB, 235 mild, 195 moderate and 176 had severe SDB. The mean (SD) QTc was 422(29), 411(26), 419 (34) and 418 (36) ms for the no SDB, mild, moderate, and severe SDB groups, respectively (p=0.017). The mean (SD) STVQT was 7 (9), 11 (16), 8 (9) and 9 (11) for the no SDB, mild, moderate severe SDB groups, respectively (p=<0.001). The mean (SD) STVQT was 3 (2), 4 (4), 4 (3) and 4(4) for the no SDB, mild, moderate severe SDB groups, respectively (p=<0.001). There was no statistically linear relationship between QT prolongation or QT variability and SBD severity. Conclusion: QTc duration and QT variability were not increased with SDB severity. Support (if any): American Academy of Sleep Medicine Foundation (203-JF-18), National Institutes of Health (HL126140), University of Arizona Health Sciences Career Development Award (5299903), and University of Arizona Faculty Seed Grant (5833261)